A highly unsaturated six-vertex amido-substituted silicon cluster. Issue 23 (19th May 2020) - Keuter, Jan; Schwermann, Christian; Hepp, Alexander; Bergander, Klaus; Droste, Jörn; Hansen, Michael Ryan; Doltsinis, Nikos L.; Mück-Lichtenfeld, Christian; Lips, Felicitas
Abstract : Thermal treatment of the bicyclo[1.1.0]tetrasilatetraamide [Si4 {N(SiMe3 )Dipp}4 ] 1 resulted in the formation of a highly unsaturated six-vertex silicon cluster [Si6 {N(SiMe3 )Dipp}4 ] 2 with only four amine-substituents and two ligand-free silicon atoms. Abstract : Thermal treatment of the bicyclo[1.1.0]tetrasilatetraamide [Si4 {N(SiMe3 )Dipp}4 ] 1 resulted in the formation of a highly unsaturated six-vertex silicon cluster [Si6 {N(SiMe3 )Dipp}4 ] 2 with only four amine-substituents and two ligand-free silicon atoms. In solution, a major and a minor conformer of this cluster are in equilibrium according to multinuclear NMR spectroscopy, lineshape analysis, DFT calculations and molecular dynamics simulations. The bonding situation in the highly unsaturated cluster features lone pair type character at the ligand-free silicon atoms and partial single and double bond character in the upper butterfly-shaped ring of 2 . This allows to consider 2 as the silicon analogue of a butalene isomer.